2020
DOI: 10.1016/j.brs.2019.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of transcranial magnetic and direct current stimulation in children: Prospective single center evidence from 3.5 million stimulations

Abstract: Background: Non-invasive brain stimulation is being increasingly used to interrogate neurophysiology and modulate brain function. Despite the high scientific and therapeutic potential of non-invasive brain stimulation, experience in the developing brain has been limited. Objective: To determine the safety and tolerability of non-invasive neurostimulation in children across diverse modalities of stimulation and pediatric populations. Methods: A non-invasive brain stimulation program was established in 2008 at o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 53 publications
6
93
0
2
Order By: Relevance
“…These findings are supported by an extensive literature that has presented the adverse effects of most incidents in children and adolescents frequently classified as mild, such as itching, tingling, and headaches (Krishnan et al, 2015;Moliadze et al, 2015;Ciechanski and Kirton, 2017). Also, a recent study with more than 600 tDCS sessions on children and adolescents did not find severe adverse effects, being tingling and itching the most common adverse effects reported in 37% of tDCS sessions (Zewdie et al, 2020).…”
Section: Safetysupporting
confidence: 71%
“…These findings are supported by an extensive literature that has presented the adverse effects of most incidents in children and adolescents frequently classified as mild, such as itching, tingling, and headaches (Krishnan et al, 2015;Moliadze et al, 2015;Ciechanski and Kirton, 2017). Also, a recent study with more than 600 tDCS sessions on children and adolescents did not find severe adverse effects, being tingling and itching the most common adverse effects reported in 37% of tDCS sessions (Zewdie et al, 2020).…”
Section: Safetysupporting
confidence: 71%
“…genetic modification). In contrast, tDCS is safe 2 , 62 , 63 and broadly used even on healthy subjects 64 , 65 .…”
Section: Discussionmentioning
confidence: 99%
“…In the last 14 years, there have been a few very important safety reviews for tDCS in adults [2,3,5,6] and children [5,7,19]. The first from Poriesz et al [2] in 2007 reported the frequency of side effects during and after tDCS in 102 participants across 567 sessions and demonstrated that tDCS is only associated with very minor side effects such as scalp tingling (70.6%), itching (30.4%), and fatigue (35.3%).…”
Section: Current Safety Evidencementioning
confidence: 99%